TNFα inhibitors reduce bone loss in rheumatoid arthritis independent of clinical response by reducing osteoclast precursors and IL-20 - Al-Bogami, M; Bystrom, J; Clanchy, F; Taher, TE; Mangat, P; Williams, RO; Jawad, AS; Mageed, RA (Oxford University Press, 2020)
Objectives About half of RA patients treated with TNFα inhibitors either do not respond or lose their initial therapeutic response over time. The clinical response is measured by reduction in DAS28, which primarily reflects inflammation. However, other effects of TNFα inhibitors, such as impact on bone erosion, are not assessed by DAS28. We aimed to examine the effect of TNFα inhibitors on bone density, bone biomarkers and cytokine production in responder and non-responder patients and assessed mechanisms of action.